Understanding knowledge sharing activities through the use of social media tools in higher educational institutions - Hamid, Sawsan Ali; Mohd Yusof, Shafiz Affendi; Mohd Nadzir, Maslinda (JMEST, 2016)
Knowledge sharing is a process where individuals mutually exchange their knowledge and jointly create new knowledge. Several of the previous studies found that besides face-to-face interactions, students also share their knowledge through social media tools. Social media tools are currently considered as the key value in the campus to facilitate knowledge sharing and the main tasks in order to support the daily communication. Although the importance of using these tools among the students in educational institutions, many dimensions of knowledge sharing in social media environments have not yet been examined. Furthermore, many questions are still unanswered and need to be explored across different social media tools. Additionally, literature also stressed the need to focus more on use the social media with education in developing countries. For this purpose, this empirical study sought to explore the knowledge sharing activities among local and international postgraduate students at one of public universities in Malaysia, as well as find the benefits and barriers through using social media tools during sharing knowledge. With regard to data collection, the best manner to understand the perspective of the students about some of the new phenomena through harness qualitative approach. Data were collected through qualitative approach. More specifically, a total of 12 postgraduate students were interviewed and received answers from them through semi-structure interviews. Interpretive analysis method was used to find the themes via using NVivo qualitative data analysis software. The results for this study included four sections based on Nonaka and Takeuchi theory. The findings indicated that, the activities for students include exchange experience and perspective as well as confirmed the importance of social media in overcome time, geographical distance and cost that is a barriers to share knowledge as well as provide more confident to share ideas for students.This study contributed by using the Nonaka and Takeuchi model with higher educational institutions. In the same context, there are few empirical studies focused on the Information technology with knowledge sharing, therefore this research sought to add valuable information into the literature by shedding light the barriers and the benefits through utilize the new technologies to share know among the team work.